Selected works of Jawaharlal Nehru - Nehru, Jawaharlal; Gopal, S (Ed.); Kumar, Ravinder (Ed.) (New Delhi Jawaharlal Nehru Memorial Fund, 2001)
The current volume of the selected works of Jawaharlal Nehru deals with the period from 1 Oct.1954 to 31 Jan. 1955.It reaches out to crucial developments in the global community particularly in respect of Sino-Indian relations,Avadi-Session of the Congres
Contents: V.28 (1st Feb-31 May 1955)
Keywords: Nehru, Jawaharlal-Speaches, addresses etc; Literature-Collection, Indian essays